Teacher education in the 21st century - Rashmi Kumar,Ed; Subhash Chander,Ed; Bharti,Ed (Sage, 2018)
"The book provides a valuable insight for teachers and teacher-educators to act on the demands of teaching in the 21st century and helps them develop their pedagogical practices accordingly. Teacher Education in the 21st Century presents a series of focused ideas and classroom plans along with real-life examples for enhancing the quality of teacher preparation efforts to develop young minds for the future. The editors and contributors have incorporated principles of constructive teaching, inclusive education and integration of technology throughout the book. The book explicitly contextualizes the teaching practices and pedagogies in the social, cultural and linguistic landscape of India. The learning pedagogies, resource ideas, case studies, flow charts and classroom activities in this book lay the essential groundwork for teachers and teacher-educators to apply in their daily teaching. The examples and case studies span across teaching contexts in primary, middle and high school grade levels"--